2022
DOI: 10.3390/jfmk7010027
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Physical Activity Behaviors and Relationships with Fitness in the Army Training at High Intensity Study

Abstract: United States Army soldiers must meet physical fitness test standards. Criticisms of the Army Physical Fitness Test (APFT) include limited testing of only aerobic and muscular endurance activity domains; yet, it is unclear what levels of aerobic and muscle strengthening activity may help predict performance in aspects of the new Army Combat Fitness Test (ACFT). This study explored relationships between baseline self-reported aerobic and muscle strengthening activities and APFT- and ACFT-related performance. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…This echoed earlier research with ROTC cadets that found total APFT performance was not significantly associated with BMI or BF% [ 42 ]. Thus, our findings present novel fitness performance results for our study sample of mostly Army officers and add to our previous findings that greater physical activity levels were also predictive of APFT performance [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This echoed earlier research with ROTC cadets that found total APFT performance was not significantly associated with BMI or BF% [ 42 ]. Thus, our findings present novel fitness performance results for our study sample of mostly Army officers and add to our previous findings that greater physical activity levels were also predictive of APFT performance [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
“…This study used baseline data from a large five-year CRCT, the Army Training at High Intensity Study (ATHIS), one of the largest ever conducted to assess outcomes of the Army’s training program compared to a high-intensity functional training intervention among Army officers, an often-understudied population [ 24 ]. Participants were primarily recruited from the CGSC and Combined Arms Center at Fort Leavenworth, KS ( n = 115) due to the installation’s willingness to collaborate with the research team and the fact that the population would remain at the same post over the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Fuerza resistencia de tren superior. Las dominadas o pull ups se realizaron en base a los procedimientos utilizados por el ejército de los Estados Unidos (Heinrich et al, 2022). En una barra metálica ubicada a 2,30 m de altura, se contabilizaron las ejecucio-nes correctas cuando el participante extendía por completo los brazos y luego pasaba su barbilla sobre la barra sin rea-lizar movimientos pendulares con su cuerpo.…”
Section: Composición Corporalunclassified
“…Aerobic capacity was examined in three investigations, while the anaerobic capacity was investigated in one (Koropanovski et al, 2022;Lockie et al, 2022;Perroni et al, 2022;Koropanovski et al, 2022). Muscular strength was evaluated in four articles (Heinrich et al, 2022;Talaber et al, 2022;Post et al, 2022;Perroni et al, 2022), muscular endurance was evaluated in one paper (Lockie et al, 2022), and muscular power was evaluated in three publications (Lockie et al, 2022;Post et al, 2022;Heinrich et al, 2022). Other aspects of physical fitness such as agility and flexibility were evaluated with just one test (Koropanovski et al, 2022;Post et al, 2022;Lockie et al, 2022), respectively.…”
Section: Physical Fitness Parametersmentioning
confidence: 99%
“…In their study designs, they did not include many tests or questionnaires assessing health parameters. Some vital measures such as blood pressure and high/low-density lipoprotein are some of the other health indicators studied (Heinrich et al, 2022). There is just one published study (Tomczak et al, 2022) that makes use of the IPAQ.…”
Section: Measures Of Health Featuresmentioning
confidence: 99%